Analysis of Determinants of Food Security in the Provinces of Java and Sumatra Islands 2019-2022 - Istadi, Vicky Sukma Putra; Hastuti, Sri Rahayu Budi (Journal of International Conference Proceedings, 2023)
Food has always been a strategic topic in development at both the global and national levels, because fulfilling food is a right for every citizen whose quantity and quality must be guaranteed in a safe and nutritious manner. The main problem in realizing food security in Indonesia today is related to the growth in demand for food which is faster than the growth in supply. This research aims to find out the influence of food security determinants in the provinces of Java and Sumatra Islands in 2019-2022. By using secondary data and panel regression,Fixed Effect Model is the best model chosen to be used in this research. Partially, rice land productivity, population and agricultural labor have a significant effect on food security in the provinces of Java and Sumatra Islands. Together or simultaneously the variables of rice land productivity, population and agricultural labor have an influence on food security. There is a need for efforts and an active role from the government and society in optimizing the implementation of policies related to the protection of agriculture and human resources in order to maintain sustainable food security.